Dynamic modelling and small signal stability analysis of voltage source converter-based HVDC system. (2016) - Nayak, N.; Dash, P.K.; Rout, Pravat Kumar
In this paper, the modelling of the entire VSC-HVDC system is presented based on d-q axis decomposition and state space modelling is formulated for analysis. Eigenvalues analysis is used for optimal tuning of PI controller based on PSO technique. The system is simulated under most of the frequently occurring faults and abnormal operating conditions such as three-phase fault, parameter variation, frequency variation and change in active and reactive power, change in short circuit ratio and bus voltage reduction and change in converter parameters through MATLAB simulation. The results are presented for the proposed controller with comparison to conventional PI controller under various fault condition.